IMPORTANCE OF COMPETENT BASED APPROACH SO AS TO IMPROVE LISTENING SKILLS OF STUDENTS AT HIGHER EDUCATION - Abdukhakimova Kamola Akmalovna, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
The improvement of listening abilities is seen as a crucial part of communicative ability in contemporary foreign language instruction. However, a lack of efficient teaching methodologies makes it difficult for many students in higher education institutions to grasp spoken English. Listening skills are typically neglected in favor of grammar and reading exercises in traditional language instruction approaches. In this regard, the competency-based approach has become a successful teaching method for enhancing students' practical language skills. This study aims to investigate the significance of the competency-based approach in improving students' listening abilities in higher education. The study examines how competency-based teaching approaches enhance understanding, encourage active learning, and assist students in using listening techniques in everyday conversation.  A range of interactive, student-centered activities, including problem-solving listening exercises, group projects, and actual audio resources, were used to assist the development of listening skills. The results demonstrate that the competency-based approach significantly enhances students' motivation, listening comprehension, and ability to comprehend spoken content under a variety of conditions. This approach also encourages students to develop unique learning strategies and improves their general language abilities. The findings show that using competency-based methods in foreign language instruction can significantly improve students' listening abilities in higher education.